INCIDENCE OF ANTIBIOTIC RESISTANCE IN METHICILLIN RESISTANT STAPHYLOCOCCUS AUREUS IN BURN PATIENTS IN A TERTIARY CARE HOSPITAL, INDIA. - VIRENDRA S KOLHE,; SANJAY R MORE,; SANTOSH M MANGALKAR, (International Journal of Pharma and Bio Sciences, 2014)
Staphylococcus aureus infection remains an increasing problem of hospital acquired infections in burn patients, among them methicillin resistant Staphylococcus aureus poses potential cause of morbidity and mortality. Our study was carried out at the Department of Microbilogy at GMC Latur, India. From Jan 2012 to June 2013, to determine the profile of aerobic bacterial infection in burn patients. Total 353 samples from 277 patients were analyzed. Staphylococcus aureus was isolated in total 70 samples (18.22%), out of these 43 (61.42%) were Methicillin resistant Staphylococcus aureus (MRSA) as determined by cefoxitin disc. Methicillin resistant Staphylococcus aureus (MRSA) showed the maximum sensitivity to vancomycin and linezolid. While, MRSA showed the maximum resistant pattern to commonly used antibiotics, was responsible for most nosocomial infection.